2023
DOI: 10.3390/su15031748
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Nexus and Circular Economy to Decouple Carbon Emissions from Economic Growth

Abstract: Experts have been searching for ways to mitigate the impacts of climate change on resources since the early 20th century. In response, the World Economic Forum introduced the concept of a “nexus”, which involves the simultaneous, systematic collaboration of multiple individuals or sectors, such as water, energy, and food, in order to create an integrated approach to reducing resource scarcity through a multi-disciplinary framework. In contrast, a circular economy (CE) involves restructuring material flows from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 148 publications
0
4
0
Order By: Relevance
“…From such an exciting outcome, it is clear that the specified economies have achieved a certain technological level and are on the right path to secure their biodiversity. Similarly, this outcome can compare with the findings of [ [85] , [86] , [87] ]. Similarly, Khan et al [ 86 ], described the case study of Netherlands and argued that higher authorities had taken the initiative to utilize waste in green energy generation and other sustainable production & consumption activities at the domestic level.…”
Section: - Results and Discussionmentioning
confidence: 63%
“…From such an exciting outcome, it is clear that the specified economies have achieved a certain technological level and are on the right path to secure their biodiversity. Similarly, this outcome can compare with the findings of [ [85] , [86] , [87] ]. Similarly, Khan et al [ 86 ], described the case study of Netherlands and argued that higher authorities had taken the initiative to utilize waste in green energy generation and other sustainable production & consumption activities at the domestic level.…”
Section: - Results and Discussionmentioning
confidence: 63%
“…Despite the circular economy's goal of reducing waste and encouraging the use of more environmentally friendly products, this may lead to more emissions. These results highlight the need for more study into the connection between industrial ecology and carbon emissions in this setting and emphasize the need to consider the circular economy's economic and environmental consequences [ 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unsustainable urbanization is creating difficulties which is expected to double by 2050. The world is facing resource scarcity along with a rising population the catastrophe is emerging with environmental degradation which is a challenging task for the policy makers to ensure sustainability 29 . Reference 30 probe the ten energy efficient countries to gauge the impact of energy efficiency on economic growth to mitigate environmental degradation and found that energy intensity has a positive impact on economic growth and degraded environment whereas energy efficiency bears the potential to reduce GHGs by about 40%.…”
Section: Literature Reviewmentioning
confidence: 99%